A new species of Amazonia (black mildews) on Ixora brachiata from Western Ghats, India - Mohamed, Hina; Thomas, Jacob (Phytotaxa, 2021)
A new species of black mildew fungi was discovered infecting leaves of Ixora brachiata (Rubiaceae). The new species is described as Amazonia brachiata and it is the first record of an Amazonia species on I. brachiata. It is documented in detail with description, line drawings and photo plate, and is morphologically compared to similar species previously reported on the host family. A key to Amazonia species found on Rubiaceae is included to aid in their identification.